Childhood Mental Disorders and Subsequent Adverse Outcomes in Early Adulthood: A Population-Based Longitudinal Study - Chartier, Mariette; Bolton, James; Ekuma, Oke; Mota, Natalie; Hensel, Jennifer; MacWilliam, Leonard; Nie, Yao; McDougall, Chelsey (International Journal of Population Data Science, 2018)
Introduction The relationship between childhood/adolescent mental disorders and adult outcomes has been studied using surveys and clinical samples. These studies are prone to selection, recall and self-reporting biases. No previous studies have used population-based administrative databases linking individual-level data that could address these biases and further elucidate this relationship. Objectives and Approach Using de-identified administrative databases housed at the Manitoba Centre for Health Policy, we aimed to determine whether people diagnosed with mental disorders in childhood/adolescence, compared to those without, were at higher risk of early adverse adult outcomes. We created a birth cohort of 60,838 residents of Manitoba, Canada, born from fiscal years 1980/81 to 1984/85 and followed them to the end of study period in 2014/15. Through a scrambled health identifier, health, education, social services and justice system data were linked at an individual level. Survival analysis was used to test for differences controlling for key childhood covariates. Results We found that 16.5% of the cohort had a diagnosed mental disorder at some point in their childhood/adolescence. Having a diagnosed mental disorder in childhood/adolescence increased the risk of being diagnosed with the same disorder in early adulthood (at age 30 to 34 years old). It also increased the risk of suicidal death (hazard ratio (HR): 2.41), suicide attempts (HR: 3.05), public housing use (HR: 1.44), income assistance use (HR: 2.07), criminal accusation (HR:1.53), and criminal victimization (HR:1.54) in adulthood. Similarly, but to a greater extent, suicide attempts in adolescence increased the risk of suicidal death (HR: 3.65), suicide attempts (HR: 5.68), public housing use (HR: 1.64), income assistance use (HR: 1.68), criminal accusation (HR: 2.18), or criminal victimization (HR: 2.43) in adulthood. Conclusion/Implications Young people’s mental health has significant influence on their health and well-being trajectories into adulthood. This knowledge could directly inform policy and practice to provide better population-based mental health promotion, prevention and early interventions for children/adolescents with mental disorders and subsequently prevent adverse adult outcomes in the future.